Find expert advice and community support for all your questions on IDNLearn.com. Discover the reliable solutions you need with help from our comprehensive and accurate Q&A platform.
Sagot :
Answer:
x = -1, 7
Step-by-step explanation:
Given question is incomplete; find the complete question in the attachment.
x² - 6x - 7 = 0
Step 1,
Isolate the constant by ADDING 7 both the sides of the equation.
x² - 6x - 7 + 7 = 0 + 7
x² - 6x = 7
Step 2
Add 9 to both sides of x² - 6x = 7 to form a perfect square trinomial while keeping the equation balanced.
x² - 6x + 9 = 7 + 9
Step 3
Write the trinomial x² - 6x + 9 as (x - 3) squared.
x² - 2(3)x + 9 = 16
(x - 3)² = 4²
Step 4
Use the square root property of the equality to get x - 3 = ± 4
(x - 3)² = 4²
[tex]\sqrt{(x-3)^2}=\sqrt{4^2}[/tex]
(x - 3) = ±4
Step 5
Isolate the variable to get solution of -1 and 7
x - 3 = ± 4
x = -3 ± 4
x = -1, 7
Answer:
1. Isolate the constant by adding 7 to both sides of the equation.
2. Add 9 to both sides of x2 – 6x = 7 to form a perfect square trinomial while keeping the equation balanced.
3. Write the trinomial x2 – 6x + 9 as x – 3 squared.
4. Use the square root property of equality to get x – 3 = ± 4.
5. Isolate the variable to get solutions of –1 and 7.
Step-by-step explanation:
just completed this on edge
We appreciate every question and answer you provide. Keep engaging and finding the best solutions. This community is the perfect place to learn and grow together. Thank you for visiting IDNLearn.com. We’re here to provide clear and concise answers, so visit us again soon.